Mechanical aortic valve prostheses offer a survival benefit in 50–65 year olds: AUTHEARTVISIT study. (30th December 2021) - Traxler, Denise; Krotka, Pavla; Laggner, Maria; Mildner, Michael; Graf, Alexandra; Reichardt, Berthold; Wendt, Ralph; Auer, Johann; Moser, Bernhard; Mascherbauer, Julia; Ankersmit, Hendrik Jan
Abstract: Background: The present population‐based cohort study investigated long‐term mortality after surgical aortic valve replacement (AVR) with bioprosthetic (B) or mechanical aortic valve prostheses (M) in a European social welfare state. Methods: We analysed patient data from health insurance records covering 98% of the Austrian population between 2010 and 2018. Subsequent patient‐level record linkage with national health data provided patient characteristics and clinical outcomes. Further reoperation, myocardial infarction, heart failure and stroke were evaluated as secondary outcomes. Results: A total of 13, 993 patients were analysed and the following age groups were examined separately: <50 years (727 patients: 57.77% M, 42.23% B), 50–65 years (2612 patients: 26.88% M, 73.12% B) and >65 years (10, 654 patients: 1.26% M, 98.74% B). Multivariable Cox regression revealed that the use of B‐AVR was significantly associated with higher mortality in patients aged 50–65 years compared to M‐AVR (HR = 1.676 [1.289–2.181], p  < 0.001). B‐AVR also performed worse in a competing risk analysis regarding reoperation (HR = 3.483 [1.445–8.396], p  = 0.005) and myocardial infarction (HR = 2.868 [1.255–6.555], p  = 0.012). However, the risk of developing heart failure and stroke did not differ significantly after AVR in any age group. Conclusions: Patients aged 50–65 years who underwent M‐AVR had better long‐term survival, and a lower risk of reoperation and myocardial infarction. Even though anticoagulation is crucial in patients with M‐AVR, we did not observe significantly increased stroke rates in patients with M‐AVR. This evident survival benefit in recipients of mechanical aortic valve prostheses aged <65 years critically questions current guideline recommendations.